Effects of container size and growth medium on stock plant productivity of Heuchera 'Snow Angel' and Zauschneria garrettii 'PWWG01S' ORANGE CARPET® - Brown, Shana, author; Klett, Jim, advisor; Kelaidis, Panayoti, committee member; Barbarick, Ken, committee member (Colorado State University. Libraries, 2018)
To view the abstract, please see the full text of the document.